The carbon club : how a network of influential climate sceptics, politicians and business leaders fought to control Australia's climate policy - Wilkinson, Marian, 1954- (Allen & Unwin, 2020)
The inside story of how a network of influential climate sceptics, politicians and business leaders fought to control Australia's response to the climate crisis.